THE INFLUENCE OF STRESS LEVELS ON THE QUALITY OF LIFE OF DERMATOVENEROLOGICAL PATIENTS (World Bulletin of Public Health, 2024)
Today, skin diseases are classified as psychosomatic pathologies. For this purpose, studying the concept of “stress” and determining its impact on the quality of life of dermatovenerological patients represents an urgent problem for the healthcare system. Considering that the connection between disorders of the nervous system and skin diseases has been known for a long time, diagnosing disorders in the psycho-emotional sphere of the patient has always remained problematic, therefore changes in the psychological status of patients with various dermatoses were classified as secondary phenomena, and were considered a consequence of the underlying disease.